Performance of Synchronized and Unsynchronized Pilots in Finite Massive MIMO Systems - Mahyiddin, W.A.W.M.; Martin, P.A.; Smith, P.J. (2015)
Pilot contamination occurs when cells simultaneously transmit the same pilot sequences, creating interference. Unsynchronizing the pilots can reduce pilot contamination, but it can produce data to pilot interference. In this paper, we investigate the impact of pilot contamination and other interference, namely data to pilot interference, on the performance of finite massive MIMO systems with synchronized and unsynchronized pilots. Two unsynchronized pilot schemes are considered. The first is based on an existing time-shifted pilot scheme, where pilots overlap with down-link data from nearby cells. The second time-shifted method overlaps pilots with uplink data from nearby cells. Results show that if there are small numbers of users, the first time-shifted method provides the best sum rate performance. However, for higher numbers of users, the second time-shifted method has advantage compared to other methods. We also show that time-synchronized pilot is not necessarily the worst case scenario in term of sum rate performance when shadowing effect are considered.